Role of body mass index in burns: Influence on mortality, hospital stay, and wound infections - K. Prasanna; Shiva Siddhartha Sonti; P. Nellaiappar; T. Alia Hussain (Indian Journal of Burns, 2024)
Introduction: While obesity is conventionally recognized as a risk factor for increased mortality and morbidity among trauma patients, a growing body of evidence suggests the existence of an intriguing phenomenon known as the “obesity paradox.” It is worth noting that current medical literature contains limited data concerning the impact of body mass index (BMI) on individuals who have suffered severe burn injuries. Burn injuries remain a significant challenge in developing countries, despite remarkable advancements in their management. Aims and Objectives: The primary objective was inhospital mortality. Secondary objectives were hospital stay and wound infections. Materials and Methods: This was a prospective study from June 2022 to November 2022 in the Department of Burns, Plastic, and Reconstructive Surgery, Kilpauk Medical College and Hospital. Results: Difference in hospital stay did not reach statistical significance (P = 0.26). Wound infection in this study (P = 0.87) was not significant. BMI in this study was 27.01 ± 4.76. Mortality in BMI group >30 kg/m2 was more than <30 kg/m2; P = 0.03 which was significant (Fischer’s exact test calculator). Conclusion: Our findings reveal a notable increase in mortality rates among obese patients, with a discernible “inflection point” when their BMI surpasses 30 (kg/m2). This particular insight bears significant relevance for burn care teams, prompting them to refine their approaches and minimize adverse outcomes in this patient group.